Effectiveness of toric soft contact lenses for vision correction in patients with different degrees of astigmatism: a real-world study - Guo-Yun Zhang; Lu Ye; Wen-Jun Wang; Yi-Ming Guo; Jun-Han Wei; Mei-Xia Ren (International Journal of Ophthalmology, 2023)
AIM: To assess the visual correction of patients with different degrees of astigmatism with toric soft contact lenses (TSC). METHODS: It was a real-world study with prospective and single-arm design. A total of 384 patients with astigmatism who came for TSC fitting and alignment from November 2022 to January 2023 were included. According to the difference in astigmatism, patients were divided into groups A (cylinder degree: -0.75 to -0.50 D), B (cylinder degree: -1.75 to -1.00 D) and C (cylinder degree ≤ -2.00 D), and followed up on the day of wear, 1wk, 1 and 3mo, mainly to observe visual acuity, refraction, lens fit, visual quality and comfort at 1wk after wear. The visual acuity success rate and the overall success rate of the fitting were evaluation indicators (taking into account the four dimensions of visual acuity, fitting, quality of vision and comfort). The visual acuity success rate was calculated by taking “corrected visual acuity with contact lenses is no less than 1 line or better than best spectacle-corrected visual acuity” (i.e. corrected visual acuity with contact lenses is 1 line below, equal to, one line above or more than best spectacle-corrected visual acuity) as the criterion for visual success, and the the overall success rate of the fitting was calculated by using the comprehensive indicators (visual acuity, fit, visual quality, comfort) to meet certain conditions as the judgment criteria for successful fitting. RESULTS: After 1wk of wearing TSC, the visual acuity success rates of patients were 100% (207/207), 98.58% (139/141) and 97.22% (35/36) in the three groups, respectively, with residual cylinder closed to 0. The acceptability of the lens fitting was over 95%; the incidence of adverse visual symptoms was within 10% and the comfort acceptability was over 97%. The overall success rate of fitting for patients with high, medium and low astigmatism was 93.72% (194/207), 90.78% (128/141) and 88.89% (32/36), respectively. CONCLUSION: TSC (model: G&G POP·CT) are effective in correcting astigmatism in patients with different degrees of astigmatism.